PARTISIPASI PEDAGANG DALAM PENGELOLAAN SAMPAH - Yuriani ., Lampus; Welson M. Wangke; Martha M. Sendow (Sam Ratulangi University, 2017)
This study aims to determine the participation of market traders in waste management in Pasar Pinasungkulan Manado City. This research was conducted at Pasar Pinasungkulan Manado City located in Karombasan Urban of Manado City. This research was conducted for 3 months from January 2017 until March 2017. Sources of data taken in this research are primary and secondary data. Primary data was obtained through interviews with traders. Secondary data is obtained from PD Pasar Paal Dua office. The sampling method used in this research is the accidental sampling method, which is self-determined of 92 respondents. The data analisis was descriptive based on table of frequency. Based on the results of descriptive analysis it can be seen that the index of market participant participation is high enough with the score obtained is 1.827.